Jane Doe's Mission: A Serious-Critical Digital Game for Web Designers and Developers to Train Web Accessibility for Screen Readers - Guilherme João Albuquerque Vila Maior (2024)
Despite significant technological advancements, web accessibility remains underpracticed amongst web designers and developers, resulting in obstacles for users who rely on screen readers. These users often face confusing and disorganized content, which not only hinders their navigation, but can also cut it short. This study investigates how a Serious-Critical game can raise awareness about screen reader accessibility while supporting players with educational resources to improve accessibility practices by addressing the gap in web accessibility practices and exploring challenges faced by blind users while examining the web accessibility practices and gaming preferences of web designers and developers. The research employed a Human Centered Design approach, and it begins with a comprehensive literature review on the evolution, benefits and challenges of web accessibility. It also explores how and why Serious and Critical Games influence players' thinking, reaction and reflection process. Quantitative research involved the creation and dissemination of 2 online surveys amongst: blind web users to mainly collect data on the frequency of encountering obstacles online and the subsequent feeling of frustration; and web designers and developers to collect the target audience's habits and preferences on gaming and web accessibility practices. Focus group sessions with blind users provided qualitative comprehension and insight on the web interactions and accessibility obstacles that they face. Next, we applied a co-design session, with participants from design and interaction/game design backgrounds, using card sorting activities to achieve results that contributed to the creation of the final game. Ultimately, the conceptualized game aims to raise players' awareness on the web accessibility and challenges faced by screen reader users, and to support the player with educational material on the Web Content Accessibility Guidelines 2.2 to practice and enhance their web accessibility skills, particularly, towards screen readers.